Small RNA-Seq to Characterize Viruses Responsible of Lettuce Big Vein Disease in Spain - Bernal-Vicente, Agustina; Donaire, Livia; Torre, Covadonga; Gómez-Aix, Cristina; Sánchez-Pina, Maria Amelia; Juarez, Miguel; Hernando, Yolanda; Aranda, Miguel A. (Frontiers in Microbiology, 2018)
The emerging lettuce big-vein disease (LBVD) is causing losses in lettuce production ranging from 30 to 70% worldwide. Several studies have associated this disease with Mirafiori lettuce big-vein virus (MiLBVV) alone or in mixed infection with lettuce big-vein associated virus (LBVaV). We used Illumina small RNA sequencing (sRNA-seq) to identify viruses present in symptomatic lettuce plants from commercial fields in Southern Spain. Data analysis using the VirusDetect tool showed the consistent presence of MiLBVV and LBVaV in diseased plants. Populations of MiLBVV and LBVaV viral small RNAs (sRNAs) were characterized, showing features essentially similar to those of other viruses, with the peculiarity of an uneven asymmetric distribution of MiLBVV virus-derived small RNAs (vsRNAs) for the different polarities of genomic RNA4 vs. RNAs1 to 3. Sanger sequencing of coat protein genes was used to study MiLBVV and LBVaV phylogenetic relationships and population genetics. The Spanish MiLBVV population was composed of isolates from three well-differentiated lineages and reflected almost all of the diversity reported for the MiLBVV species, whereas the LBVaV population showed very little genetic differentiation at the regional scale but lineage differentiation at a global geographical scale. Universal primers were used to detect and quantify the accumulation of MiLBVV and LBVaV in field samples; both symptomatic and asymptomatic plants from affected fields carried equal viral loads, with LBVaV accumulating at higher levels than MiLBVV.